The objectives of this research were to determine and to compare the physical and mechanical properties of OSB made of strands from three small diameter fast growing species, namely Akasia (Acacia mangium Willd.), Ekaliptus (Eucalyptus sp.), and Gmelina (Gmelina arborea Roxb.). There were 3 models of OSB produced which bonded by 2 types of adhesive, namely Phenol Formaldehyda (PF) powder type, isocyanate (IC), and the face and back layers bonded by powder PF and the core layer bonded by IC. OSB - Arif NURYAWAN; Muh. Yusram MASSIJAYA; Yusuf Sudo HADI (Departemen Hasil Hutan, IPB, 2008)
The objectives of this research were to determine and to compare the physical and mechanical properties of OSB made of strands from three small diameter fast growing species, namely Akasia (Acacia mangium Willd.), Ekaliptus (Eucalyptus sp.), and Gmelina (Gmelina arborea Roxb.). There were 3 models of OSB produced which bonded by 2 types of adhesive, namely Phenol Formaldehyda (PF) powder type, isocyanate (IC), and the face and back layers bonded by powder PF and the core layer bonded by IC. OSB was made of three plies, with 9 mm target thickness and ratio of strands weight in face : core : back was 1:1:1. Mat forming methods in face was lengthwise and the core was widthwise. Level of adhesive 7% based on oven dry strands weight, pressed at 25 kg/cm2 for 15 minutes at 160 °C. Japanese Industrial Standard (JIS) A 5908-2003 for particle board 24-10 type was used as standard. Results of this research showed generally physical properties consist of density, moisture content, and thickness swelling fulfilled JIS A 5908-2003 standard. Unfortunatelly, the dimensional stability should be improved, the range 24 hours water absorption was about 22.35–44.63%. For mechanical properties, which consist of internal bonding, modulus of rupture (MOR) and modulus of elasticity (MOE) which be evaluated in dry condition both lengthwise and widthwise generally fulfilled JIS A 5908-2003 standard. However, there were values of MOR and MOE which be evaluated in wet condition both of lengthwise and widthwise did not fulfill JIS A 5908-2003 standard. The best performance of OSB was which bonded by IC for all the wood species. Using PF powder at the face and back layers and IC in the core layer of OSB generally increased their physical properties (dimensional stability) but decreased their mechanical properties. Keywords : Physical and mechanical properties, OSB, small diameter fast growing species, adhesive